Exercise-mediated downregulation of MALAT1 expression and implications in primary and secondary cancer prevention - Paronetto, Maria Paola; Dimauro, Ivan; Grazioli, Elisa; Palombo, Ramona; Guidotti, Flavia; Fantini, Cristina; Sgrò, Paolo; De Francesco, Dario; Di Luigi, Luigi; Capranica, Laura; Caporossi, Daniela (Free radical biology & medicine, 2020)
Long non-coding RNAs (lncRNAs) play critical roles in various biological functions and disease processes including cancer. The metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was initially identified as a lncRNA with elevated expression in primary human non-small cell lung tumors with high propensity to metastasize, and subsequently shown to be highly expressed in numerous other human cancers including breast, ovarian, prostate, cervical, endometrial, gastric, pancreatic, sarcoma, colorectal, bladder, brain, multiple myeloma, and lymphoma. MALAT1 is deeply involved in several physiological processes, including alternative splicing, epigenetic modification of gene expression, cellular senescence, healthy aging, and redox homeostasis. The aim of this work was to investigate the modulation exerted by a single bout of endurance exercise on the level of MALAT1 expression in peripheral blood mononuclear cells (PBMCs) from healthy male donors displaying different training status and redox homeostasis features. Our findings show that MALAT1 is downregulated after acute endurance exercise in subjects whose fitness level guarantee a high expression of SOD1 and SOD2 antioxidant genes and low levels of endogenous oxidative damage. In vitro protocols in Jurkat lymphoblastoid cells exposed to pro-oxidant environment confirmed the link between MALAT1 expression and antioxidant gene modulation, documenting p53 phosphorylation and its recruitment to MALAT1 promoter. Remarkably, analyses of Microarray-Based Gene Expression Profiling revealed high MALAT1 expression in leukemia patients in comparison to healthy control and a significant negative correlation between MALAT1 and SOD1 expression. Collectively our results highlight the beneficial effect of a physically active lifestyle in counteracting aberrant cancer-related gene expression programs by improving the redox buffering capacity. [Display omitted] •The lncRNA MALAT1 is deeply involved in cancer as well as several physiological processes, including redox homeostasis.•MALAT1 is downregulated after acute endurance exercise in PBMCs from subjects whit high SOD1 and SOD2 gene expression.•Jurkat lymphoblastoid cells exposed to sustainable H2O2 concentration show MALAT1 promoter inhibition through p53 phosphorylation.•Leukemia patients show higher MALAT1 expression than healthy controls with negative correlation between MALAT1 and SOD1 expression.•A physically active lifestyle could counteract aberrant cancer-related gene expression by improving the redox buffering capacity.